Efeito da terapia laser de baixa potência no tratamento da síndrome da ardência bucal : ensaio clínico, randomizado, placebo-controlado - Spanemberg, Juliana Cassol (2015)
Burning mouth syndrome (BMS) is a complex disease characterized mainly by symptoms of burning, pain or itching in the oral mucosa without apparent clinical alterations. The literature was reviewed in the first manuscript, emphasizing BMS characteristics, etiology and therapeutics. Low-level laser therapy (LLLT) has been widely used in oral disorders because of its analgesic, anti-inflammatory and tissue repair effects. Thereby, in the second manuscript we reviewed the applicability and protocols of LLLT in the management of lichen planus, xerostomia, recurrent aphthous stomatitis, herpes labialis, oral mucositis and BMS. Controlled trials investigating the effects of LLLT on BMS are still rare. The present randomized, placebo-controlled study aimed to clinically assess the effect of LLLT in the treatment of patients with BMS, and to investigate the impact of such therapy in the quality of life of these individuals. The sample consisted of 78 BMS patients who were randomly assigned into three laser groups and one control group (n=19), which was treated with sham LLLT. Laser groups were treated with the following parameters: IR1w group, n=20 (830 nm, 100 mW, 5 J, 176 J/cm2, 50 s, weekly LLLT sessions, ten sessions); IR3w group, n=20 (830 nm, 100 mW, 5 J, 176 J/cm2, 50 s, three weekly LLLT sessions, nine sessions); red laser group, n=19 (685 nm, 35 mW, 2 J, 72 J/cm2, 58 s, three weekly LLLT sessions, nine sessions). Symptoms were assessed at initial, at the end of the treatment and eight weeks later using visual analogue scale and visual numeric scale. Quality of life related to oral health was assessed through the Oral Health Impact Profile (OHIP-14). Statistical analysis was carried out using repeated measures ANOVA followed by the Tukey test. There was a significant reduction in the symptoms in all groups at the end of the treatment, which was maintained in the follow-up. The scores of the IR1w and IR3w laser groups were significantly lower in comparision to the control group. On the other hand, there was no significant difference between Red laser group and control group. There was also a decrease in the OHIP-14 scores in the four groups. The scores of the IR3w laser group differed significantly from those of the control group, showing that LLLT had a positive impact on the quality of life related to oral health. Based on the results of this study it is possible to conclude that infrared LLLT, in the parameters used, reduces the BMS symptoms and can be an alternative therapeutic for this disorder.